Epidemiological Study of Cases of Death Due to Drowning at Mortuary of North Bengal Medical College Hospital - Jagadish Biswas; Vivek Kumar; Tenzing Zampel Bhutia; Prabir Kumar Deb; Mrinal Kanti Jha (Institute of Medico-legal Publications Pvt Ltd, 2021)
Drowning is a mode of asphyxia which literally means, ‘suffer death by submersion in water or any other liquid’ or ‘suffocation by submersion in water or any other liquid because of being unable to breath’. As per WHO, in 2015, an estimated 360 000 people died from drowning, making drowning a major public health problem worldwide. We have conducted this study in Morgue of North Bengal Medical College, Siliguri to find out the demographic profile of drowning cases of North Bengal Region. In this study we have analysed the 55 cases of drowning deaths autopsied in the mortuary of Department of Forensic Medicine, NBMCH, Darjeeling, West Bengal in the last one year from 1st January 2020 to 31st December 2020. All data were analysed by appropriate statistical tools like SPSS software. In this study we found that most of the cases belong to young adult age group (29%) and cases are mostly of males (82%). In the month of July to September (34.54%) cases of drowning deaths were high and most of deceased died due to fall inside the well (43 %). Incidence of drowning deaths were mostly seen between 12 noon to 4 pm (60%) and 89.09 % cases of drowning deaths occurred immediately after the incidence.